Effects of long and short ejaculatory abstinence on sperm parameters: a meta-analysis of randomized-controlled trials - Lo Giudice, Arturo; Asmundo, Maria Giovanna; Cimino, Sebastiano; Cocci, Andrea; Falcone, Marco; Capece, Marco; Abdelhameed, Ali Saber; Capogrosso, Paolo; Morgado, Afonso; Tsampoukas, Georgios; Manfredi, Celeste; Russo, Giorgio Ivan (Frontiers in Endocrinology, 2024)
Purpose This study aimed to investigate the effects of ejaculatory abstinence on sperm parameters. Methods This analysis was registered in PROSPERO (CRD42023472124). We performed a search on PubMed using the following text terms: ((“sperm parameters” OR “sperm analysis” [Mesh]) AND (“sperm DNA fragmentation” OR “DNA fragmentation” [Mesh]) AND (“sexual abstinence” [Mesh] OR “abstinence”)) and an advanced search in Scopus using the terms (“sperm parameters” OR “sperm parameters” OR “DNA fragmentation”) AND (“abstinence”). The sperm parameters that were investigated were sperm volume, total sperm motility, progressive sperm motility, sperm concentration, sperm morphology, and sperm DNA fragmentation (SDF). A two-day cut-off as a “short” or “long” abstinence period has been defined. Results Thirteen studies published between 2013 and 2022 were included in this meta-analysis. A total of 2,315 patients, ranging from 6 to 836 from each cohort, were enrolled in the study. We showed that longer abstinence time was associated with greater sperm concentration (mean difference [MD]: 8.19; p <0.01), sperm volume (MD: 0.96; p <0.01), and higher SDF (MD: 3.46; p <0.01), but lower progressive sperm motility (MD: −1.83; p <0.01). Otherwise, no statistically significant difference was observed in patients with longer vs. shorter abstinence times regarding total sperm motility (MD: −1.83; p = 0.06). Meta-regression analysis showed that days of abstinence were positively and linearly related to sperm concentration (slope: 3.74; p <0.01) and SDF (slope: 0.65; p = 0.044). Conclusions According to our data, short ejaculatory abstinence is associated with better sperm quality. Indeed, a higher percentage of progressive sperm motility and lower levels of SDF have been reported in a short abstinence cohort. In contrast, the long abstinence group reported a higher sperm concentration. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023472124.